2015
DOI: 10.1371/journal.pone.0131782
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Is an Independent Risk Factor for Hospital-Acquired Pneumonia

Abstract: BackgroundPatients who were hospitalized for community-based pneumonia frequently had pre-existing atrial fibrillation (AF) and had subsequent cardiovascular complications. Whether patients who had AF would be susceptible to the development of hospital-acquired pneumonia (HAP) is a serious concern but this has not been investigated. In our clinics, we have made empirical observation of such susceptibility.ObjectivesTo investigate the association between newly developed HAP and pre-existing AF, and to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 19 publications
4
37
2
3
Order By: Relevance
“…However, gender, smoking, CHD, DM, rheumatic heart disease, non-rheumatic valvular disease, myocardiopathy/myocarditis, hyperlipidemia, electrolyte disturbance and congenital heart disease were not significant risk factors for HAP (ref. 12 ). Another study of ICU patients with HAP in association with Staphylococcus aureus showed that significant risk factors are diseases such as liver cirrhosis or DM.…”
Section: Discussionmentioning
confidence: 99%
“…However, gender, smoking, CHD, DM, rheumatic heart disease, non-rheumatic valvular disease, myocardiopathy/myocarditis, hyperlipidemia, electrolyte disturbance and congenital heart disease were not significant risk factors for HAP (ref. 12 ). Another study of ICU patients with HAP in association with Staphylococcus aureus showed that significant risk factors are diseases such as liver cirrhosis or DM.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al proposed that atrial fibrillation was an independent risk factor for HAP [25]. In Guzmán-Herrador et al's study, decreased level of consciousness on admission was a risk factor for HAP [26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dysphagia increases length of hospital stay 1.8 times in patients with CHF [4]. Moreover, Zhu, et al have shown that high blood pressure and heart failure are important risk factors for hospital-acquired pneumonia in cardiovascular inpatients, and that contracting hospital-acquired pneumonia significantly increases morbidity, mortality, hospitalization stays, and total medical costs [5]. It is suspected that CHF is strongly related to dysphagia.…”
Section: Introductionmentioning
confidence: 99%